2017
DOI: 10.18411/2500-1701-2017-12-1-142-147
|View full text |Cite
|
Sign up to set email alerts
|

The Results of the First Researches of Zoobenthos in Lake Shchebety (Transbaikalia

Abstract: Результаты первых исследований зообентоса озера Шебеты (Забайкалье) 3 В июле 2016 г. на озере Шебеты проведены первые исследования озёрного зообентоса таежной зоны южной части Забайкальского края. В материалах исследования зообентос представлен 36 таксонами. Основу таксономического разнообразия составили хирономиды (37 %) и олигохеты (17 %). 69 % видов обнаружено в литоральной зоне до глубины 5 м. Здесь отмечены потенциально новые для науки виды рода Vejdovskyella Mishaelsen, 1903. В фаунистическом отношении п… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The long-term hydrobiological study results of some mountain lakes in the Baikal basin are revealed in monographs (Pleshanov, 2009;Timoshkin, 2009) and other papers (Bondarenko, 2009;Matveev et al, 2010). Some integrated research results of Lake Shebety are listed by Tsybekmitova et al (2016), Afonina & Tashlykova (2017), Matafonov & Andrievskaya (2017), Gorlacheva (2019).…”
Section: Introductionmentioning
confidence: 99%
“…The long-term hydrobiological study results of some mountain lakes in the Baikal basin are revealed in monographs (Pleshanov, 2009;Timoshkin, 2009) and other papers (Bondarenko, 2009;Matveev et al, 2010). Some integrated research results of Lake Shebety are listed by Tsybekmitova et al (2016), Afonina & Tashlykova (2017), Matafonov & Andrievskaya (2017), Gorlacheva (2019).…”
Section: Introductionmentioning
confidence: 99%